Pengaruh Kualitas Pelayanan, Promosi, dan Harga Terhadap Kepuasan Pelanggan Melalui Loyalitas Pelanggan Pengguna Transportasi Ojek Online Gojek di Daerah Khusus Jakarta - Shania Arnita; Daman Sudarman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to test the phenomenon of research to find out how many factors influence the influence of service quality, promotion and price on customer satisfaction through customer loyalty of Gojek online motorcycle taxi transportation users in the Special Region of Jakarta. This research uses quantitative descriptive analysis methods and is associative in nature. This research data was obtained through distributing questionnaires which were measured using a Likert scale, which would then be processed through data processing methods with the SmartPls device. The sample in this study amounted to 280 respondents using the probability sampling method and taking a representative sample from the population whose sample was used or taken from a population that truly represents the existing population. The results of the research show that service quality has a positive and significant effect on customer satisfaction, promotion has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, promotion has a positive and significant effect on customer loyalty , price has a positive and significant effect on customer loyalty, and customer satisfaction has a positive and significant effect on customer loyalty.